PENGARUH PENAMBAHAN UNSUR TEMBAGA PADA PENGECORAN TEKAN BLOK SILINDER BEKAS TERHADAP NILAI IMPAK DAN KEAUSAN : EFFECT OF ADDITION OF COPPER ELEMENTS IN THE COMPRESSION CASTING OF USED CYLINDER BLOCKS ON IMPACT VALUE AND WEAR - Sinarep; Agus Dwi Catur; Mujiantara Daeng Permana; Ahmad Zainuri (Energy, Materials and Product Design, 2024)
The cylinder liner block is part of the cylinder block which functions as a place for the engine working process to take place. Where in this section the suction, compression, work and exhaust processes occur. Cylinder blocks have two types, some can be repaired and cannot be repaired, to utilize cylinder blocks that cannot be repaired by recycling them by casting metal with copper (Cu) with variations in the addition of 5%, 10%, 15% with a casting temperature of 1150⁰C using metal molds using the press technique method. Data collection was carried out by wear testing, impact testing, and microstructure testing. By increasing the percentage of copper (Cu) in the cylinder block casting, the highest wear was obtained with the addition of 15% Cu of 2,87×10-9 m3. The highest impact strength of 15% Cu is 0.12 Joule/mm2.